Seasonal variation in the incidence of primary intracerebral hemorrhage: a 16-year nationwide analysis - Baig, Eman; Tannous, Jonika; Potter, Thomas; Pan, Alan; Prince, Taya; Britz, Gavin; Vahidy, Farhaan S.; Bako, Abdulaziz T. (Frontiers in Neurology, 2023)
Introduction Data on nationwide trends and seasonal variations in the incidence of Intracerebral Hemorrhage (ICH) in the United States (US) are lacking. Methods We used the Nationwide Inpatient Sample (2004–2019) and Census Bureau data to calculate the quarterly (Q1:January-March; Q2:April-June; Q3:July-September; Q4:October-December) incidence rates (IR) of adult (≥18 years) ICH hospitalizations, aggregated across Q1–Q4 and Q2–Q3. We report adjusted incidence rate ratios (aIRR) and 95% confidence intervals (CI) for differences in the quarterly incidence of ICH, as compared to acute ischemic stroke (AIS), between Q1Q4 and Q2Q3 using a multivariable Poisson regression model. We additionally performed stratified analyses across the four US regions. Results Among 822,143 (49.0% female) ICH and 6,266,234 (51.9% female) AIS hospitalizations, the average quarterly crude IR of ICH was consistently higher in Q1Q4 compared to Q2Q3 (5.6 vs. 5.2 per 100,000) (aIRR, CI: 1.09, 1.08–1.11)—this pattern was similar across all four US regions. However, a similar variation pattern was not observed for AIS incidence. The incidence (aIRR, CI) of both ICH (1.01, 1.00–1.02) and AIS (1.03, 1.02–1.03) is rising. Conclusion Unlike AIS, ICH incidence is consistently higher in colder quarters, underscoring the need for evaluation and prevention of factors driving seasonal variations in ICH incidence.